Readiness of PV-Hydrogen: An environmental sustainability analysis in Sulawesi - Tjatur Udjianto; Teguh Sasono; Wildan Arasid; Rolf Gisler (Education and Development Research, 2026)
In line with the Indonesian Government's efforts to achieve decarbonization and net-zero emissions before 2060, the transition from fossil fuels to renewable energy sources has been increasingly pursued. One of the technologies employed is the hydrogen-to-power application, which promotes the utilization of photovoltaic generators, batteries, and hydrogen, particularly in Eastern Indonesia (PV-Hydrogen). The objective of this study is to obtain feasibility recommendations for the PLN (State Electricity Company) network in Sulawesi that will be used for distributing electricity generated from PV-Hydrogen through power flow studies, short-circuit current studies, and system stability analysis. This study was conducted to ensure the readiness and capability of the existing network in accommodating PV-Hydrogen generators. The power flow simulation results for the Selayar system indicate that under existing conditions, some end-of-feeder loads exhibit voltage drops still within the range above 18 kV, with the farthest point at Appatana having the lowest voltage at approximately 18.21 kV. The existing 20 kV network is generally ready to receive power supply from renewable energy generators, particularly PV-Hydrogen. To accommodate this integration, a switching substation or express feeder needs to be constructed to distribute power from PV-Hydrogen. The savings or reduction in carbon emissions resulting from replacing diesel power plants with PV-Hydrogen is approximately 128,665 tons of CO2/year.